Charcot’s famous secretaries - Teive, Hélio Afonso Ghizoni; Germiniani, Francisco Manoel Branco; Munhoz, Renato Puppi; Walusinski, Olivier (Arquivos de Neuro-Psiquiatria, 2017)
At the pinnacle of his career, Professor Charcot had four secretaries: Charles Féré, Pierre Marie, Georges Gilles de la Tourette and Georges Guinon. They helped the great founder of neurology with his activities at La Salpêtrière Hospital and his private clinic, examining patients before he made the final diagnosis.
Keywords: neurology; history; Charcot